Applying Finite-Element and Boundary-Element Methods to Select Rational Design Version of Weld-Fabricated Bogie Frame Brackets of Locomotives and Railway Cars - O. A. Rusanov; V. V. Kochergin; A. A. Bukhantsev; V. V. Brekson (Вестник Научно-исследовательского института железнодорожного транспорта)
There is proposed method to select rational design version of weld-fabricated bogie frame brackets of locomotives and railway cars. The selection is performed in accord with the outcomes of double-phase computation-based stress analysis in the welded joints. At the first stage general stressed state of a bogie frame as a whole is examined by applying finite-element method. At the second stage special features of 3D stress distribution within the individual bracket are studied in detail using boundary-element method with due regard for factors of geometric concentration of stresses within the potential welding defects zones. Loading conditions of bogie frame fragment with a bracket simulated on the individual basis are very close to those of its loading while within the frame. They are selected according to the results of stresses examination in the frame carried out with use of its comprehensive model. Comparative analysis of bracket design versions is performed by varying form, dimensions and location of welded joints and type of edge preparation. Geometry of connected details may also be varied. The design version may be added with some details. In all the simulation cases there ought to be identical loading and fixing conditions as well as modeling techniques applied to brackets, welds and stress concentrators. There is assessed effect exerted on stresses by one factor only, specifically design version of an assembly under consideration. Efficiency of the proposed method may be exemplified by selection of rational design version for weld-fabricated axle-box links bracket of electric locomotive bogie frame. The method is made use of in refining a design of weld-fabricated bogie frames of electric locomotives.